The Distributional Impact of the 1970 Recession - Mirer, Thad W. (The Review of Economics and Statistics, 1973)
PpT HE loss of aggregate income due to the 1970 recession in the United States is widely recognized and much decried. How the loss has been distributed in society is not so well known and not extensively researched. This paper is concerned with measuring and describing the incidence of the recession on families, by income level. Historical trends in the size distribution of income have been' analyzed by Budd (1970) and Lampman (1971), and its cyclical variability has been studied by Schultz (1969), Metcalf (1972), Thurow (1970), and Mirer (1972). Most of their results suggest that macro-economic downturns increase income inequality or otherwise bear heavily on the poor and near-poor. This analysis examines micro data from a panel survey to measure the pattern of incidence of the loss of aggregate income in 1970, and finds it to be different from the effects found for past recessions. Toward the end of the 1960's, the economy was experiencing high employment along with increasing inflation. Restrictive monetary and fiscal policies along with changes in the structure of government expenditure brought about a worsening of economic conditions. In February 1969 the civilian unemployment rate stood at 3.3 per cent; it rose above 3.5 per cent in September and above 4.0 per cent in February 1970. By December 1970 the unemployment rate was 6.1 per cent. In 1970 real output declined 0.4 per cent from the 1969 level. In describing the distributional effects of these changes in macro-economic conditions, it is essential to compare what actually occurred to what would have occurred under some specified set of alternative conditions. The analytical framework of this study is a comparative statics model in which families' incomes in 1970 are compared to what their incomes would have been then if the aggregate conditions of 19671969 had continued. This approach is particularly relevant for policy purposes because it allows one to judge the distributional costs of the restrictive anti-inflationary policies of recent years.